A study on the incidence of tuberculosis in Narail district of Bangladesh - Mallick, MS (Mediscope, 2018)
The aim of this descriptive type of study on diagnosed tuberculosis (TB) cases was to evaluate the incidence of TB in Narail district to have a situational analysis with the achievement of National TB Control Program. Related data were collected from the Civil Surgeon Office, Narail district. The data of 3 upazilas- Narail Sadar, Kalia, and Lohagora were used. The study period was from January 1, 2016 to December 31, 2016. The overall TB case rate was 156.6 per 100000 population and separately 170.9 per 100000 population in Narail Sadar, 142.2 per 100000 population in Kalia and 156.6 per 100000 population in Lohagora. Of the cases, 56.4% were male and 43.6% female. Overall, 89.7% of the TB cases had pulmonary TB and 10.3% had extra-pulmonary TB. The population with higher age had higher proportion having TB. The highest number of patients were referred for diagnosis by sastha sebika (nurse) and non-government field staff. The TB incidence in Narail district was considered to be lower than the National situation. However, it seems that TB will remain as a continuous concern for many years in future for the country as well as Narail district. The activities of National TB Control Program of the Government of Bangladesh needs to be strengthened further to combat TB in Bangladesh Mediscope Vol. 5, No. 2: Jul 2018, Page 12-15